2016
DOI: 10.1016/j.agee.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous preferences and the effects of incentives in promoting conservation agriculture in Malawi

Abstract: Journal articleIFPRI3; CRP2; ISIEPTD; PIMPRCGIAR Research Program on Policies, Institutions, and Markets (PIM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…More specifically, government subsidies [88,92,119] and credits or loans [70] were found to be positively correlated with adoption of BMPs. Prokopy et al [98] surveyed farmers in the Eagle Creek watershed of Central Indiana and found that all farmers interviewed were motivated by financial gain, albeit to various degrees.…”
Section: Financial Incentivesmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, government subsidies [88,92,119] and credits or loans [70] were found to be positively correlated with adoption of BMPs. Prokopy et al [98] surveyed farmers in the Eagle Creek watershed of Central Indiana and found that all farmers interviewed were motivated by financial gain, albeit to various degrees.…”
Section: Financial Incentivesmentioning
confidence: 99%
“…He found that conservation education training is the primary tool available to effect practice change. Extension services provide timely and effective information on practices as well as new technologies [76,88,101,102], and proximity to extension agents increases adoption [101]. Atwell et al [47], Kalcic et al [104] and Woods et al [62] found that interactions with local conservation staff frequently are positively correlated with adoption.…”
Section: Information and Awareness Of Bmpsmentioning
confidence: 99%
“…This is a model of CA advocacy that has since been replicated across Malawi and has cumulatively acted to sustain a high-input form of CA, a practice that regional meta-analyses suggest are an appropriate route to enhancing maize yields in low rainfall areas (Rusinamhodzi et al, 2011). This alignment can explain the reticence of farmers to shift to, or stick with, CA practices, when subsidies for agricultural inputs are not available (Ward et al, 2015); or when they are faced with additional labour requirements for the basin planting systems advocated in no till systems (Bunderson et al, 2002;Thierfelder et al, 2016).…”
Section: The Institutional Environment Of Conservation Agriculturementioning
confidence: 99%
“…Dyer et al, 2013). In the case of CA in Malawi, the role of NGOs, donors and/or the private sector in providing financial support (or input subsidies) to smallholder farmers as outgrowers can be particularly influential given their ability to provide short-term incentives (Ward et al, 2015) when the longer-term impact on maize yields remains difficult to determine and explain. This is particularly important given that regional meta-analyses suggest that the main benefit of CA is increased stability of crop yields in dry climates (Rusinamhodzi et al, 2011;Brouder and GomezMacpherson, 2014;Giller et al, 2015).…”
Section: Research Priorities and Institutional Support For Sustamentioning
confidence: 99%
See 1 more Smart Citation